Effect of Solvents and Extraction Conditions on the Properties of Crude Rice Bran Oil - PIMPA, Benchamaporn; THONGRAUNG, Chakree; SUTTHIRAK, Pornpong (Walailak Journal of Science and Technology (WJST), 2021)
This research aimed to study the effect of solvents, namely n-hexane and ethanol, on the yield of crude rice bran oil extraction. The effects of extraction temperatures of 50, 60, and 70 ºC and extraction times of 1, 3, 6, 12, and 24 h were investigated. Rice bran composition was determined. It was found that protein, lipid, moisture, fiber, ash, and carbohydrate content were 12.65±0.56, 16.32±0.81, 7.65±0.62, 10.25±0.64, 6.38±0.59, and 46.75 %, respectively. From the results, the rice bran oil yield from n-hexane extraction was significantly higher than ethanol extraction, with p < 0.05. The maximum rice bran oil obtained from n-hexane extraction was 16.23±0.34 %. The highest yield of rice bran oil was obtained from extraction temperature of 60 - 70 ºC for 12 - 24 h. After extraction by the optimum conditions at 60 ºC for 12 h, the rice bran oil was kept for 1, 2, 3, 4, and 8 weeks for investigation of its quality changes. It can be concluded that the optimum conditions for rice bran oil extraction was with using n-hexane as a solvent for extraction at a temperature of 60 ºC for 12 h. Storing oil for 0, 1, 2, 4, and 8 weeks resulted in the increase of free fatty acids (FFA) and peroxide value, whereas iodine value and saponification value were relatively constant. HIGHLIGHTS n-Hexane and ethanol effect the yield of crude rice bran oil extraction The rice bran oil yield from n-hexane extraction was higher than ethanol extraction The optimum conditions for rice bran oil extraction were with using n-hexane as a solvent for extraction at a temperature of 60 ºC for 12 h Storing rice bran oil for 8 weeks resulted in the increase of free fatty acids (FFA) and peroxide value, whereas iodine value and saponification value were relatively constant